Improving Behavioral Outcomes in Type II Diabetes Mellitus Patients Through Lectures Assisted by Video in the Muara Bangkahulu Community Health Center Working Area, Bengkulu City - Selvi Annisyah; Darwis; Ade Febryanti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction : Type II diabetes mellitus is a common type of disease and accounts for 85-90% of all diabetes cases that occur. There is an increase in cases of type II diabetes mellitus from year to year and there are still many sufferers who have not implemented dietary habits, physical activity, adequate rest and control blood sugar in daily life and there is still a lack of knowledge and attitudes of type II diabetes mellitus sufferers about diabetes. type II mellitus Objective : This research aims to determine the effect of lectures using educational video media on the behavior of people with type II diabetes mellitus Method : This type of research uses quantitative research methods with a pre-experiment research design and a one group pretest-posttest design. Sampling used a purposive sampling method with a total of 35 respondents. Analysis of knowledge and behavior data used the Wilcoxon test and for attitudes used the paired t-test. Result :. The results of the average knowledge of sufferers about type II diabetes mellitus were pretest 4.80 (not good), post test 7.37 (good). while the average attitude of pretest sufferers was 25.54 (negative), post test 30.11 (positive). and for the average behavior of type II diabetes mellitus sufferers pretest 11.83 (not good), posttest 14.14 (good). There was an effect of lectures using educational video media on the behavior of type II diabetes mellitus sufferers (P ? 0.05). Conclusion: The improvement in behavior among patients with type II diabetes mellitus through lectures using educational video media.